Julian DeForest Venter collection of Stonewall Jackson papers - Venter, Julian DeForest; Jackson, Stonewall, 1824-1863.
Autograph signed letter and annotated envelope (1862 June 11; headquarters Valley District) from Jackson to Union General James Shields regarding Shields's request that a Union surgeon be allowed to examine the Union wounded kept in hospitals near the battlefield of Cross Keys, Va.; letter (1862 April 1; Winchester, Va.) addressed to Shields requesting that he forward to Stonewall Jackson a petition for the release of individuals arrested prior to the occupation of Winchester, with a note on the verso referring the letter and petition to Gen. Nathaniel Prentiss Banks; letter (1862 April 10; headquarters, Dept. of the Shenandoah, Va.) from Banks to Jackson concerning the petition; and letter (1862 June 24) from Shields to Capt. Louis Henry Pelouze regarding supplies for the troops.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Banks, Nathaniel Prentiss, -- 1816-1894 -- Correspondence; Pelouze, Louis Henry -- Correspondence; Shields, James, -- 1806-1879 -- Correspondence; United States. -- Army -- Supplies and stores; Cross Keys, Battle of, Cross Keys, Rockingham County, Va., 1862.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Medical care; Virginia -- History -- Civil War, 1861-1865.; Winchester (Va.) -- History; Collectors